Possibilities of using proteomic analysis in infectiology - N. S. Strashnikova; G. P. Martynova; A. B. Salmina; R. Yа. Olovyannikova; V. A. Kutyakov; A. Tohidpur (Бюллетень сибирской медицины, 2019)
Modern methods of diagnosis and treatment of infectious diseases should be based on reliable data obtained through various methods of laboratory research. The main characteristics of the methods used are high sensitivity (the ability to analyze a small amount of sample, 10–6–10–4 g/ml), selectivity, reproducibility and others. Proteomic methods of research satisfy all the principles of evidence-based medicine. The advantages of using these methods to identify biomarkers (identifying proteins with altered expression levels), timely diagnosis and treatment of infectious diseases, described in the article, are obvious. Their introduction into practice is an element of personalized medicine.